2008
DOI: 10.1007/s11908-008-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of Cryptococcus gattii in British Columbia and the Pacific Northwest

Abstract: An unprecedented emergence of cryptococcal infections in animals and otherwise healthy humans was recognized in 1999 on the east coast of Vancouver Island, British Columbia. Unexpectedly, these infections were caused by Cryptococcus gattii, a species closely related to the AIDS-associated fungal pathogen Cryptococcus neoformans. Human cases have continued over the past 8 years and now total approximately 170 with eight deaths. Extensive environmental sampling, coupled with detailed molecular typing of isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
111
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 46 publications
1
111
1
Order By: Relevance
“…Despite its medical importance, the treatment for cryptococcosis is limited. With increasing concerns of drug resistance and evolution of new virulent strains (6)(7)(8)(9), there is an urgent need to understand the molecular basis of cryptococcal infection in order to discover and develop safer and more effective antifungal drugs. Against this background of clinical need are the heroic research efforts toward understanding the mechanism of Cryptococcus development and virulence that have significantly advanced the field in the past several decades.…”
mentioning
confidence: 99%
“…Despite its medical importance, the treatment for cryptococcosis is limited. With increasing concerns of drug resistance and evolution of new virulent strains (6)(7)(8)(9), there is an urgent need to understand the molecular basis of cryptococcal infection in order to discover and develop safer and more effective antifungal drugs. Against this background of clinical need are the heroic research efforts toward understanding the mechanism of Cryptococcus development and virulence that have significantly advanced the field in the past several decades.…”
mentioning
confidence: 99%
“…Cryptococcus is the most common systemic fungal pathogen of cats and can also cause severe disseminated disease in dogs (1). In humans, C. neoformans is opportunistic, usually infecting HIV/AIDS patients and other immunosuppressed individuals (2), whereas C. gattii is more likely to infect immunocompetent hosts (3). Cryptococcosis typically occurs in cats with no obvious underlying immunodeficiency, and infections are not associated with concurrent retroviral infection or other immunocompromised states (4,5).…”
mentioning
confidence: 99%
“…C. gattii strains that belong to molecular type VGII can be further categorized into a large number of subtypes. Of those VGIIa, VGIIb, and VGIIc have been implicated in disease in immunocompetent humans, cats, dogs, and other animal species in British Columbia and the Pacific Northwest of the United States (3,(13)(14)(15)). An epidemiological study of dogs and cats with cryptococcosis in California showed that cats were most often infected with C. gattii molecular type VGIII, whereas dogs were more likely to be infected with C. neoformans, possibly reflecting host differences in susceptibility (6).…”
mentioning
confidence: 99%
“…However, since 1999, an outbreak of C. gattii infections has been occurring in the temperate climate of Vancouver Island in British Columbia. This outbreak has resulted in at least 200 human cases and eight deaths (3,21). More recently, cases of cryptococcosis caused by C. gattii have occurred on the mainland in British Columbia as well as in Washington and Oregon in the United States.…”
mentioning
confidence: 99%